Implementasi Kepemimpinan Transformasional Dalam Meningkatkan Motivasi Kerja Guru Di Upt Sd Negeri 03 Muaradua - Riduan Riduan; Pransida Budaya; Arianda Pratama; Zainul Rifqi; Dessy Wardiah; Eni Heldayani (CV. Ulil Albab Corp, 2026)
Education has an important part in improving the human resources quality, with the principal playing a main part in managing resources and making a conducive work climate. This mini reserch purpose is analyzing and describing the implementation of the head master transformational leadership at the UPT SD Negeri 03 Muaradua and its impact on teacher work motivation. The study focuses on four main dimensions according to Bernard M. Bass: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Furthermore, this study evaluates the level of teacher work motivation, reflected in the aspects of responsibility, commitment, discipline, work enthusiasm, and professional development, and identifies supporting and inhibiting factors in their implementation. The novelty of this study lies in its location at the UPT level of elementary schools in South OKU Regency, which has rarely been studied empirically, with a particular emphasis on work motivation as the main impact variable. The results are expected providing contributions in theory, theoretically the contributions to the study of educational leadership and practical recommendations for principals to optimize leadership practices to improve the quality of studying and the professionality of teacher.